(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
This essay addresses the educational development of university teachers from a critical Latin American perspective, proposing it as an ethical and political project that contributes to overcoming the persistent inequalities that prevent the fulfillment of the human right to higher education. Its purpose is to enrich the debate on the purposes, contents and methodologies of educational development programs and initiatives, suggesting that they be oriented towards the transformation of practices that limit the participation of all social groups. In particular, the implications of the contributions of Paulo Freire, Darcy Ribeiro and Rita Segato are analyzed to think about teacher training as a transformative practice, and a strategic agenda is presented with five articulating axes to guide its renewal.